How do current police practices impact trauma care in the prehospital setting? A scoping review - Rama A. Salhi; Sonia Iyengar; Brianna da Silva Bhatia; Graham C. Smith; Michele Heisler (Journal of the American College of Emergency Physicians Open)
Abstract Objective In the United States, police are often important co‐responders to 911 calls with emergency medical services for medical emergencies. To date, there remains a lack of a comprehensive understanding of the mechanisms by which police response modifies time to in‐hospital medical care for traumatically injured patients. Further, it remains unclear if differentials exist within or between communities. A scoping review was performed to identify studies evaluating prehospital transport of traumatically injured patients and the role or impact of police involvement. Methods PubMed, SCOPUS, and Criminal Justice Abstracts databases were utilized to identify articles. English‐language, US‐based, peer‐reviewed articles published on or prior to March 30, 2022 were eligible for inclusion. Results Of 19,437 articles initially identified, 70 articles were selected for full review and 17 for final inclusion. Key findings included (1) current law enforcement practices involving scene clearance introduce the potential for delayed patient transport but to date there is little research quantifying delays; (2) police transport protocols may decrease transport times; and (3) there are no studies examining the potential impact of scene clearance practices at the patient or community level. Conclusions Our results highlight that police are often the first on scene when responding to traumatic injuries and have an active role via scene clearance or, in some systems, patient transport. Despite the significant potential for impact on patient well‐being, there remains a paucity of data examining and driving current practices.